Comparison of total and partial parenteral nutrition to achieve calorie target among treated children in the intensive care unit - Widyastuti, Syafrida; Trisnawati, Yunnie; Supriatmo, Supriatmo (Narra J, 2024)
The achievement of recommended calorie targets for parenteral nutrition in pediatric patients receiving treatment in the pediatric intensive care unit (PICU) in Indonesia remains suboptimal, necessitating cautious implementation of this nutritional intervention alone. The aim of this study was to compare the effectiveness of total parenteral nutrition (TPN) and partial parenteral nutrition (PPN) in achieving the calorie requirements of pediatric patients receiving treatments in the PICU. A cross-sectional study was conducted in the PICU at H. Adam Malik General Hospital, Medan, Indonesia, among patients aged between 28 days to 18 years. The consecutive sampling method was employed to collect samples based on predetermined inclusion and exclusion criteria. The assessments of recommended calorie achievement targets were conducted up to 240 hours after initial nutrition treatment. Other possible factors associated with the achievement of the nutrition target were also assessed between groups, such as demographic data, length of treatment, nutritional status, and underlying diseases. A total of 30 patients were included in each group (TPN and PPN). There were no significant differences in age, weight, height, sex, or underlying diseases between groups. All patients in both groups achieved the target calorie requirements after 168 hours. Our data indicated that the percentage of patients who met the target calorie requirements was significantly different at initial treatment, 72 hours, and 120 hours post-treatment between groups (all had p<0.001). The percentages of patients who met the nutritional requirements (carbohydrate and protein) were also significantly different between the TPN and PPN groups (all had p<0.001). This study highlights that the administration of PPN to children resulted in faster achievement of calorie targets compared to TPN.